2012
DOI: 10.1111/j.1365-2818.2012.03656.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional nanofabrication of polystyrene by focused ion beam

Abstract: SummaryFocused ion beam micromachining provides a maskless and resistless technique for prototyping of structures from thermoplastic polymers, an example being the production of polystyrene microcantilevers with potential applications as micro/nanoelectromechanical systems sensors and actuators. The applicability of FIB technology is, however, often restricted by the damage created by high energy gallium ion bombardment and local beam heating, which can affect the desired properties and limit the minimum achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…However, this process can introduce molecular scale changes that are detectable using transmission electron microscope (Kim et al ., ), cause local cracking of the polymer (Olea‐Mejía et al ., ), and even sufficient morphological instabilities to severely deform the geometry FIB‐prototyped nanostructures (Schmied et al ., , ; Orthacker et al ., ). For pure polymers the thermal damage localized to the ion beam impact area can be minimized using cryogenic cooling, low current milling and smart navigation of the ion beam (Kim et al ., , Bassim et al ., , Lee et al ., , Olea‐Mejía et al ., , Schmied et al ., , , Orthacker et al ., ). In the latter approach the ion beam exposure pattern is altered from the common pixelated line‐by‐line raster to increase the time in‐between re‐exposure of individual points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this process can introduce molecular scale changes that are detectable using transmission electron microscope (Kim et al ., ), cause local cracking of the polymer (Olea‐Mejía et al ., ), and even sufficient morphological instabilities to severely deform the geometry FIB‐prototyped nanostructures (Schmied et al ., , ; Orthacker et al ., ). For pure polymers the thermal damage localized to the ion beam impact area can be minimized using cryogenic cooling, low current milling and smart navigation of the ion beam (Kim et al ., , Bassim et al ., , Lee et al ., , Olea‐Mejía et al ., , Schmied et al ., , , Orthacker et al ., ). In the latter approach the ion beam exposure pattern is altered from the common pixelated line‐by‐line raster to increase the time in‐between re‐exposure of individual points.…”
Section: Introductionmentioning
confidence: 99%
“…Dual beam instruments that combine focused ion beam with a scanning electron microscope (FIB-SEM) are extensively used for characterization of various materials ranging from semiconductors to biological tissue (Stevie et al, 2005;Volkert & Minor, 2007;Bassim et al, 2014), but have not been applied to analysis of organic corrosion barrier coatings. In the past, FIB-SEM has been used for site specific cross sectioning and/or lamella extraction for transmission electron microscope imaging (White et al, 2001;Lins et al, 2002;Loos et al, 2002;Beach et al, 2005;Brunner et al, 2006Brunner et al, , 2008Brostow et al, 2007;Kawahara et al, 2008;Martínez et al, 2008;Wong et al, 2010;Firpo et al, 2015;Qin et al, 2015), destructive tomography (Kato et al, 2007;Lin et al, 2012;Olea-Mejía et al, 2012) and nanofabrication (Aubry et al, 2002;Niihara et al, 2005;Lee et al, 2012;Schmied et al, 2012;Orthacker et al, 2014;Schmied et al, 2014) of polymers and polymeric composites. Out of these examples, only a few studies have been dedicated to characterization of pristine organic coatings and paints (Lins et al, 2002;Brunner et al, 2006Brunner et al, , 2008Brostow et al, 2007;Lin et al, 2012;Chen et al, 2013;Doutre et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This technique was successfully used to prepare crosssections of polymer/metal interfaces (Faber et al, 2014). FIB is not supposed to introduce strain into the material near the interface (Kim et al, 2011;Lee et al, 2011Lee et al, , 2012Bassim et al, 2012;Schmied et al, 2012;Rivera et al, 2013). In FIB a focused beam of 30 keV Ga + ions is used to sputter material.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that FIBinduced Ga segregates onto the surface in the form of spherical droplets. [24][25][26][27][28][29] Within an hour of annealing at T a $ 773 K, most of the smaller Ga droplets disappear from the transparent regions of the sample via Ostwald ripening and are absorbed by larger droplets located at the thicker ends of the sample. 30 In situ annealing at higher temperatures T a between 1073 and 1173 K are carried out in the double C s -corrected Link€ oping FEI 80-300 Titan 3 scanning TEM (STEM) equipped with EDS and EELS spectrometers.…”
mentioning
confidence: 99%